2021
DOI: 10.1002/nur.22105
|View full text |Cite
|
Sign up to set email alerts
|

Can you hear me now?: Improving palliative care access through telehealth

Abstract: Telehealth has been increasingly used to expand healthcare access over the last two decades. However, this had not been the case for palliative care (PC), because telehealth was considered nontraditional and impractical due to the sensitive nature of conversations and a "high touch" philosophy. Motivated by limited PC access to rural and underserved populations and positive PC telehealth studies, clinical PC telehealth models have been developing. However, nearly overnight, the COVID-19 pandemic accelerated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…In the UK, for example, teleconsultation and video conferencing have been broadly used by general practitioners and palliative care teams (Antunes et al., 2020 ; Kasaraneni, 2020 ). In line with other studies, however (Allen Watts et al., 2021 ; Pastrana et al., 2021 ), these successes did not come without a cost, particularly noted with regard to the challenges to effective telehealth assessments (e.g., inability to always identify nonverbal cues) and related staff exhaustion from the additional work involved. This point illustrates that in moving forward, teleconsultation should not be seen as a replacement for visits in person but should be gradually integrated into care delivery.…”
Section: Discussionsupporting
confidence: 85%
“…In the UK, for example, teleconsultation and video conferencing have been broadly used by general practitioners and palliative care teams (Antunes et al., 2020 ; Kasaraneni, 2020 ). In line with other studies, however (Allen Watts et al., 2021 ; Pastrana et al., 2021 ), these successes did not come without a cost, particularly noted with regard to the challenges to effective telehealth assessments (e.g., inability to always identify nonverbal cues) and related staff exhaustion from the additional work involved. This point illustrates that in moving forward, teleconsultation should not be seen as a replacement for visits in person but should be gradually integrated into care delivery.…”
Section: Discussionsupporting
confidence: 85%
“…However, these services were limited to institutions and people with sufficient resources and funds. Other than financial barriers, lack of appropriate technical skills, language barriers, inability to participate, and cybersecurity were other reported concerns among the providers that may potentially reduce the acceptance and effectiveness of telehealth among patients and families 33,34 . A multisite study during the pandemic explored the effectiveness of virtual PC and reported proper equipment setup, connectivity issues, and effective communication skills as major barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patient‐focused efforts on increasing awareness, education, and access to PC information through community educational talks, articles, social media, and institutional websites are necessary, especially in minority communities where there may be stronger hesitancy toward utilizing PC. In low resource settings, utilizing telehealth services and developing pilot projects for nursing home and community‐based PC programs are key strategies to expanding PC access in these areas 31,32 …”
Section: Discussionmentioning
confidence: 99%